Values of Megibung Tradition in Tumbu Traditional Village, Karangasem, Bali: An Ethnopedagogical Study - Subyanto, Ni Putu Ari Krisnayanthi (Jurnal Pendidikan dan Pengajaran, 2022)
Bali is known for its culture and customs, one of which is the culture of â€œeating togetherâ€ activities or that is known as â€œmengibungâ€. Through this research, it will be explored the value of megibung tradition which is still found in the traditions of the people in Tumbu Traditional Village. In addition to the requirements for values, this research aims to inform young generation to preserve traditions that have been carried out since ancient times. This research uses qualitative research. The subject of this research is the community in Tumbu Traditional Village. The object of this research is Tumbu village, Karangasem. The data collection techniques used were observation, interviews, and documentation. The result of this research showed that the traditions that exist in Karangasem, precisely in Tumbu Traditional Village, is megibung tradition. Megibung tradition is as the tradition of eating together in one place by sitting in a circle consisting of 6-7 people in one side or one group. Megibung tradition contains values of togetherness, mutual cooperation, justice and have ethics in the society. Both social values, in the megibung tradition, teach us to have a sense of kinship, tolerance, and mutual cooperation in society. Three religious values in megibung tradition refer to always be grateful to God Almighty and ancestors for what has been given.